Cool hand Luke [videorecording (Blu-Ray)] - Pearce, Donn; Pierson, Frank R.; Newman, Paul, 1925-2008; Kennedy, George, 1925-2016; Cannon, J. D. (John Donovan), 1922-2005; Antonio, Lou, 1934-; Drivas, Robert, 1935-1986; Martin, Strother, 1919-1980; Van Fleet, Jo, 1914-1996; Hall, Conrad; Schifrin, Lalo; Pearce, Donn (Warner Home Video, 2008)
Lucas Jackson is a man who refuses to be nailed down, conform to rules and regulations, or fit into society, and now, he's on a chain gang. He's a likable enough guy, always smiling, always ready for a little fun. He eats 50 hard-boiled eggs on a bet and collects all the money in the camp. He's more or less like the people he hangs around with, except he won't be pushed. He knows his own mind. This makes him the only prisoner with guts enough to talk back to the bosses and the only one with nerve enough to escape. That Luke, he's a cool hand.